Capturing the role of rural consumers in sensitive price indicator through geometric consistency check on urban and rural market prices - Faraz, Humaira; Raees, Fahim; Baig, Mirza Mahmood (Mehran University research journal of engineering and technology, 2023)
This paper focuses on capturing price movement and price stability in rural and urban markets. Pakistan collects prices from both markets, but only for the computation of the Consumer Price Index (CPI), which is calculated on a monthly basis. It is proposed to include rural markets by widening the scope of the Sensitive Price Indicator (SPI), computed by the Pakistan Bureau of Statistics (PBS). The inconsistency in the prices of rural markets is observed on the basis of different measures, including descriptive and inferential statistics. Therefore, it is suggested to include rural markets as well in the SPI computation. Large numbers of head counts make transactions in rural areas, which may be taken into account for capturing the accurate weekly consumption pattern of the consumers. Prices of all SPI items were taken from urban and rural markets and checked for normality through the Kolmogorov-Smirnovand Shapiro-Wilk tests. Further, the normality was checked graphically by the Q-Q plot (Quantile-Quantile plot) and histogram. Due to the skewness of the data, non-parametric methods like the geometric coefficient of variation and the coefficient of mean deviation from the median have been applied to check the consistency of the prices in rural markets. The prices of rural markets for further framing of policy to widen the scope of capturing the movement of prices.